Norrøn metaordbok – en rapport fra en øvelse - Ekker, Mette Gismerøy; Ore, Christian-Emil (Nordiske Studier i Leksikografi, 2007)
The term Old Norse usually denotes the (written) languages used in Iceland until 1540 and in Norway until 1370. Old Norse was a weakly normalised language with a wide variety of forms. The scholarly study of Old Norse has long traditions and several dictionaries have been published. The Dictionary of Old Norse Prose (ONP) is a current major initiative but so far covering only letters A-E. J.Fritzner’s dictionary, FRI, (1883–1896,1974) and F.Jónsson’s Lexicon Poeticum, LP, (1931) still remain the major dictionaries.The dictionary group of the Medieval Nordic Text Archive (Menota) has as one of its main objectives to establish a framework for linking the disparate Old Norse lexicographic resources. The fragmented state corresponds closely to the state of the New Norwegian lexicography 10 years ago. Thus it was a natural choice to try to apply the methods and tools to Old Norse developed for the Norwegian Dictionary 2014 project (NO2014), the so called Meta Dictionary, a tool for systematizing lexicographical material for weakly normalised languages. In its basic form the Meta Dictionary is an electronic form thesaurus linking realizations of the lemmas. In this pilot project we have focused on the letter B and merged the headword lists of ONP, FRI, LP and a word list based on five lemmatised texts and 200 lemmatised charters. The process and the structure of the resulting Meta Dictionary are divided in three levels of normalisation. All the original forms are kept and made searchable. 1. Normalisation: The first step towards merging was simply to ensure one common system for normalised spelling. 2. Citation form: The wordlists follow different principles in choice of the form of the cited headword, e.g. nom.sg versus nom.pl. Consequently we had to make sure that all the wordlists use the same forms. 3. Meta level, further merging of related word forms: The last step is to connect the multitude of related word forms, both between and within lists, in meta lemmas. Such related forms can be nouns differing in gender, or small differences in word formation. We also briefly discuss the linking of the medieval material to the modern dictionary projects, like NO2014. We conclude that such a linking at least for Norwegian will involve considerable manual processing. The realization of an Old Norse Meta Dictionary should also rely on a close cooperation with the ONP project.